Development and testing of a simple field-based intermittent-flow respirometry system for riverine fishes. (23rd September 2017) - Mochnacz, Neil J; Kissinger, Benjamin C; Deslauriers, David; Guzzo, Matthew M; Enders, Eva C; Anderson, W. Gary; Docker, Margaret F; Isaak, Dan J; Durhack, Travis C; Treberg, Jason R
Abstract : Understanding variability in the physiology of stream fishes is important for predicting how populations may respond to environmental change, but obtaining these data from remote areas is challenging. We developed a field-based respirometer, suitable for remote areas because of its simplicity and combined low overall weight and power requirements, which tested favorably against a laboratory-based system for metabolic rate estimates in fish. Abstract: By understanding range-wide intraspecific variation in metabolic rate we can better understand how organisms have adapted to their environment. However, methods to quantify metabolic rate of fishes from remote areas or those that cannot be brought back to the laboratory because of imperilment status are lacking. Consequently, practical and reliable field-based methods are needed. To address this need, we developed a simple yet robust intermittent-flow respirometry system, adapted from a design commonly used in the laboratory that is readily suited for field use. Standard metabolic rate (SMR), maximum metabolic rate (MMR) and aerobic scope (AS) estimates were obtained from juvenile lake trout ( Salvelinus namaycush ) and brook trout ( Salvelinus fontinalis ) using both field- and laboratory-based systems. Whole-fish SMR, MMR and AS estimates from the field and laboratory methods did not differ from one another (ANCOVA and LMM: all P > 0.05) for either species and were comparable to estimates previously reported. Our field setup is a simpler system than the conventional laboratory-based system that requires less power and equipment to operate, yet still offers users the ability to: (1) acclimate fish to the respirometry chamber; (2) measure oxygen consumption during a shorter period (1 h), which yield metabolic rate estimates comparable to systems that take measurements over longer periods; and (3) take repeated oxygen consumption measurements with manual user-defined flush and measurement phase routines. Developing practical and reliable field respirometry methods, as demonstrated here, is important if we wish to improve our ability to predict how imperiled species will respond to changes in their environment. Such knowledge is critical for informing conservation strategies.